2016
DOI: 10.1128/jvi.02859-15
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Major and Minor Capsid Protein Variants of Human Papillomavirus 45 (HPV45): Differential Recognition by Cross-Neutralizing Antibodies Generated by HPV Vaccines

Abstract: cWe investigated naturally occurring variation within the major (L1) and minor (L2) capsid proteins of human papillomavirus genotype 45 (HPV45). Pseudoviruses (PsVs) representing HPV45 sublineages A1, A2, A3, B1, and B2 exhibited comparable particle-to-infectivity ratios and morphologies but demonstrated both increased (A2, A3, and B1) and decreased (B2) sensitivities to cross-neutralization by HPV vaccine antibodies compared to that of the A1 sublineage. Mutant PsVs identified HI loop residue 357 as being cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…HPV33 variants displayed a reduced (2- to 4-fold) sensitivity to type-specific nonavalent vaccine sera similar to that seen with cross-reactive bivalent and quadrivalent vaccine sera [9], suggesting that variant residues in the DE and FG loops alter capsid antigenicity to a range of antibody specificities. Natural variation in the HPV45 L1 capsid bestows an increased (A2, A3, B1) or reduced (B2) sensitivity to cross-reactive bivalent and quadrivalent vaccine antibodies [10]. In the present study, nonavalent vaccine antibodies demonstrated little (<2-fold) or no difference in the recognition of variants A2, A3, B1, and B2.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…HPV33 variants displayed a reduced (2- to 4-fold) sensitivity to type-specific nonavalent vaccine sera similar to that seen with cross-reactive bivalent and quadrivalent vaccine sera [9], suggesting that variant residues in the DE and FG loops alter capsid antigenicity to a range of antibody specificities. Natural variation in the HPV45 L1 capsid bestows an increased (A2, A3, B1) or reduced (B2) sensitivity to cross-reactive bivalent and quadrivalent vaccine antibodies [10]. In the present study, nonavalent vaccine antibodies demonstrated little (<2-fold) or no difference in the recognition of variants A2, A3, B1, and B2.…”
Section: Discussionmentioning
confidence: 45%
“…The biological consequences of HPV genome variants are unclear. Studies examining the potential impact of natural variation on L1 antigenicity have examined variants of HPV16 [6, 7], HPV31 [8], HPV33 [9], HPV45 [10], HPV52 [11], and HPV58 [12] and demonstrated, in some cases, variant-specific differences in sensitivity to monovalent, bivalent, and quadrivalent VLP immune sera, natural infection sera, and monoclonal antibodies (MAbs). Here, we evaluate the sensitivity of lineage and sublineage variants to neutralization by nonavalent HPV vaccine antibodies.…”
mentioning
confidence: 99%
“…On the surface of the capsid, there are 5 loops designated as BC, DE, EF, FG, and HI loop (Bisset et al, 2016). These surface exposed loops are known to be important for neutralizing antibody recognition, (Bisset et al, Buck et al, 2013) and sequence variation within the loops may affect efficiency of antibody neutralization (Godi et al, 2016;Guan J et al, 2015;Bisset et al, 2016). In this study, we have observed that the amino acid variation of HPV-45 L1 from Indonesian isolates are not showing major different in protein structure (Figure 2).…”
Section: Homology Modelling Of Hpv-45 L1 and Epitopes Predictionmentioning
confidence: 52%
“…behaviours may distinct, for example, the difference in viral infectivity, persistence, antibody recognition and progression of cervical dysplasia to cervical cancer (de Oliviera et al, 2016;Bernard et al, 2005;Burk et al, 2013;Chen et al, 2014;Godi et al, 2016;Guan et al, 2015).…”
Section: Phylogeny and In Silico Structure Analysis Of Major Capsid Pmentioning
confidence: 99%
See 1 more Smart Citation